The Implementation of Context and Language Integrated Learning Approach in the Learning Process at SMP Progressive Bumi Shalawat Sidoarjo - Lutfi Saksono Saksono; Retno Wulan Dari; Ajeng Dianing Kartika; Muhammad Farid Ilhamuddin (ABISATYA : Journal of Community Engagement, 2024)
The implementation of the Content and Language Integrated Learning (CLIL) approach in the learning process at SMP Progressive Bumi Shalawat Sidoarjo aims to integrates academic content and language learning to address the challenges of combining religious and general education in Islamic boarding schools. This community service used a participatory, training-based method with stages of planning, implementation, evaluation, and follow-up. Teacher training focused on integrating academic content with English instruction, creating CLIL-based lesson plans, and employing scaffolding techniques. Results showed improvements in teachers' understanding and readiness to implement CLIL, as well as positive impacts on teaching practices. However, challenges remain in terms of training duration and resource provision. The study concludes that CLIL is a practical approach for enhancing English proficiency and academic content comprehension while maintaining Islamic values. Continuous support and follow-up are recommended to strengthen long-term implementation.